Controversies in ureteroscopy: Wire, basket, and sheath - Rizkala, Emad R (Medknow Publications & Media Pvt Ltd, 2013)
In the last one to two decades, flexible ureteroscopy has rapidly expanded its role in the treatment of urologic stone disease. With the frequent and expanded use of flexible ureteroscopy, other ancillary instruments were developed in order to ease and facilitate this technique, such as ureteral access sheaths (UAS) and a variety of wires and baskets. These developments, along with improved surgeon ureteroscopic competence, have often brought into question the need to implement the “traditional technique” of flexible ureteroscopy. In this review, we discuss a brief history of flexible ureteroscopy, its expanded indications, and the controversy surrounding the use of UAS, wires, and baskets.